Implementation of Project-Based Learning (PjBL) Model in Science Subject for Grade V at SDN 2 Sered on Ecosystem Material - Yuniati Yuniati; Ristiana Dyah Purwandari (UM Purwokerto Press, 2025)
This study aims to examine the implementation of the Project-Based Learning (PjBL) model in the science subject for Grade V at SDN 2 Sered with ecosystem material. The research uses a qualitative approach with observation, interviews, and tests to obtain a comprehensive picture of the learning process and student learning outcomes. Data were collected through direct observation at each stage of learning, interviews with teachers and students, and tests to measure understanding of ecosystem concepts. The results show that the implementation of PjBL is carried out through three main stages: preparation, implementation, and evaluation. This model successfully increased student engagement and understanding of ecosystem material significantly. In conclusion, PjBL is an effective learning strategy that can create an enjoyable and meaningful science learning experience for Grade V students at SDN 2 Sered.